Influences of Wind Energy Integration into the Distribution Network. (11th November 2013) - Shafiullah, G. M.; Oo, Amanullah M. T.; Ali, A. B. M. Shawkat; Stojcevski, Alex
Abstract : Wind energy is one of the most promising renewable energy sources due to its availability and climate-friendly attributes. Large-scale integration of wind energy sources creates potential technical challenges due to the intermittent nature that needs to be investigated and mitigated as part of developing a sustainable power system for the future. Therefore, this study developed simulation models to investigate the potential challenges, in particular voltage fluctuations, zone substation, and distribution transformer loading, power flow characteristics, and harmonic emissions with the integration of wind energy into both the high voltage (HV) and low voltage (LV) distribution network (DN). From model analysis, it has been clearly indicated that influences of these problems increase with the increased integration of wind energy into both the high voltage and low voltage distribution network; however, the level of adverse impacts is higher in the LV DN compared to the HV DN.